(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In connection with the transition to new forms of farming, the role of crafts in everyday life began to change. However, the main traditions of Kyrgyz crafts, passed down from generation to generation, from father to son, from mother to daughter, have been preserved for centuries. One of the most beautiful things that Kyrgyz craftswomen create are mat products.The most important material for making mat decorations is chiy. It grows in almost all regions of Kyrgyzstan. A plant that grows in arid semi desert areas with little fresh water. Rosinka grows at the foot of the mountains and in tree hollows. The main decoration of the interior of the yurt - the main dwelling of nomads, including the Kyrgyz, during the period of nomadic agriculture, is the use of decorative elements, which are a wonderful example of craftsmanship. The decorative elements of the yurt are the wing, door, door frame, door frame and door. In fact, the decorations of the yurt “chiy” are made, as the name suggests, from the plant “chiy”.